Differential Roles of Engrailed Paralogs in Determining Sensory Axon Guidance and Synaptic Target Recognition - Marie, Bruno (J Neurosci, 2003)
The transcription factor Engrailed (En) controls axon pathfinding and synaptic target choice in an identified neuron (6m) of the cockroach cercal sensory system. Knock-out of En using double-stranded RNA interference (dsRNAi) transforms 6m so that it resembles a neighboring neuron that normally does not express the en gene, has a different arbor anatomy, and makes different connections. Like many animals, the cockroach has two En paralogs, Pa-En1 and Pa-En2. In this study we tested the hypothesis that the paralogs have different effects on axon guidance and synaptic target recognition, using RNAi to knock out each one individually. Using dye injections into 6m and intracellular recordings from target interneurons, we obtained evidence that both Pa-En1 and Pa-En2 determine the axonal arborization, but only Pa-En1 controls synaptic connections. However, because immunocytochemical quantification of En protein in 6m after RNAi showed that Pa-En1 represents 65% of the total En activity and Pa-En2 only 35%, our results could be caused by dosage effects. We measured the effects of diluting the mixture of both dsRNAs on the amounts of En protein. From this dose-response curve, we calculated the appropriate dilutions of the dsRNA mixture that would titrate total En protein to levels equivalent to knock-out of either paralog. RNAi using these dilutions showed that Pa-En1 and Pa-En2 both contribute toward the control of axonal guidance and confirmed that Pa-En1 has the paralog-specific function of controlling synaptic target recognition.